A red laser based on perovskite structure and preparation method thereof

By adopting the F-P cavity mode and multi-layer reflective layer structure in the perovskite laser, combining nickel-oxide-doped scandium elements as the hole transport layer and magnesium-doped zinc oxide as the electron transport layer, the problems of low carrier migration efficiency and unstable hole transport layer are solved, and a red laser with high output power and efficiency is realized.

CN119231314BActive Publication Date: 2025-05-02Shandong Huaguang Optoelectronics Co. Ltd.
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411718549.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-05-02
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The carrier migration efficiency of existing perovskite lasers is low, resulting in low output power and efficiency, and the hole transport layer is unstable under acidic conditions, high threshold current and low output power.

Method used

The F-P cavity mode is used as the resonant cavity. By increasing oscillation in the working medium, the laser is used to increase the output power of the laser beam. The reflective layer is composed of alternate stacked HfO2 and SiO2 layers. The hole transport layer is a nickel-oxide-doped scandium element, the perovskite active layer is a CsPbBrI2/PbSe heterojunction layer, the electron transport layer is a magnesium-doped zinc oxide layer, and the N-plane electrode is designed with an air circulation channel.

Benefits of technology

The perovskite quantum dot carrier transmission efficiency is improved, the output power and efficiency of the red laser is improved, the construction and preparation method is simplified, the heat dissipation performance is improved, the threshold current is reduced, and the photoluminescence intensity and output power are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119231314B_ABST
    Figure CN119231314B_ABST
Patent Text Reader

Abstract

The present invention provides a red light laser based on a perovskite structure and a preparation method thereof, belonging to the field of semiconductor quantum dot lasers. The red light laser of the present invention sequentially includes, from bottom to top: a reflective layer, a P-side electrode, a hole transport layer, a perovskite active layer, an electron transport layer, and an N-side electrode; the reflective layer is formed by alternately stacking HfO2 layers and SiO2 layers; the hole transport layer is scandium-doped nickel oxide; the perovskite active layer is a CsPbBrl2 / PbSe heterojunction layer. The laser of the present invention improves the carrier transport efficiency of perovskite quantum dots in the active region, and improves the output power and efficiency of the red light laser; using the F-P cavity mode as the resonant cavity, the output power of the laser beam is increased by increasing the oscillation in the working medium. The red light laser of the present invention has the advantages of simple structure, simple preparation method, good heat dissipation, high luminous efficiency, high photoluminescence intensity, low threshold current, and high output power.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a red light laser based on a perovskite structure and a preparation method thereof, and belongs to the field of semiconductor quantum dot lasers. Background Art

[0002] Organic-inorganic halide perovskites exhibit impressive photovoltaic performance and have also been found to be potential optical gain media. However, the inherent instability of these hybrid perovskites may stifle commercial aspirations. Recently, newly designed all-inorganic cesium lead halide (CsPbX 3 (X = Cl, Br, and I) perovskite nanocrystals have reemerged as a superior optical gain material due to their large optical absorption cross-section, large exciton binding energy, high photoluminescence quantum yield, and relatively low AR loss. Importantly, these all-inorganic perovskite nanocrystals are much more environmentally durable than their organic-inorganic analogs. Compared to traditional metal chalcogenide quantum dots, CsPbX 3 Perovskite nanocrystals have the characteristics of narrow emission spectrum, simple manufacturing process, easy anion exchange color adjustment, and excellent optical gain characteristics. 3 Perovskite nanocrystals are expected to be a promising solution for future cheap laser sources.

[0003] In order to enhance the carrier migration efficiency of perovskite as the active area of ​​the chip, Chinese patent document CN111162446A developed an electrically pumped perovskite laser through spin coating and thermal evaporation technology. This laser design achieves extensive contact between the reflective layer and the transmission layer, maximizes the utilization of the working material, and allows the light beam to vibrate effectively throughout the working area. This laser using perovskite as a luminescent material has high laser quality and high color purity due to its adjustable band gap, high absorption coefficient, high optical gain, high quantum yield and low defect state density. Despite this, the structure of the invention is still relatively complex, especially the structure of the resonant cavity is relatively complex; the luminous efficiency of the perovskite active area still has room for improvement, and the photoluminescence intensity needs to be further improved; the hole transport layer uses PEDOT:PSS, etc., which is unstable under acidic conditions and has unique hygroscopic properties that inhibit the hole transport efficiency, resulting in a high threshold current of the laser and a low output power. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a red laser based on a perovskite structure and a preparation method thereof. The laser of the present invention improves the carrier transmission efficiency of the perovskite quantum dots in the active region, and improves the output power and efficiency of the red laser; the FP cavity mode is used as the resonant cavity, and the output power of the laser beam is increased by increasing the oscillation in the working medium. The red laser of the present invention has the advantages of simple structure, simple preparation method, good heat dissipation, high luminous efficiency, high photoluminescence intensity, low threshold current, and high output power.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A red laser based on a perovskite structure, comprising, from bottom to top, a reflective layer, a P-surface electrode, a hole transport layer, a perovskite active layer, an electron transport layer and an N-surface electrode;

[0007] The reflective layer is made of HfO 2 Layer and SiO 2 The layers are stacked alternately; the hole transport layer is nickel oxide doped with scandium; the perovskite active layer is CsPbBrl 2 / PbSe heterojunction layer; the electron transport layer is a zinc oxide layer doped with magnesium; the N-side electrodes are arranged on both sides of the upper surface of the electron transport layer, and the middle of the N-side electrodes on both sides is an air circulation channel.

[0008] According to the preferred embodiment of the present invention, the thickness of the reflective layer is 250-350 nm, HfO 2 The single layer thickness of the SiO 2 The single layer thickness of the layer is 15-25 nm; HfO 2 The layer is close to the lower surface of the P-side electrode. Preferably, the thickness of the reflective layer is 300nm, and the HfO 2 The single layer thickness of the SiO 2 The thickness of the single layer is 20 nm. The setting of the reflective layer is intended to improve the light output efficiency of the laser.

[0009] According to the preferred embodiment of the present invention, the P-side electrode is ITO conductive glass with a thickness of 250-350 μm. The core material of the P-side electrode is indium tin oxide, and the P-side electrode plays the role of current injection to ensure the normal operation of the laser.

[0010] Preferably according to the present invention, the molar amount of scandium element in the hole transport layer is 4-6% of the molar amount of nickel oxide, preferably 5%; the thickness of the hole transport layer is 150-250 nm, preferably 200 nm.

[0011] Preferably according to the present invention, the thickness of the perovskite active layer is 100-200 nm, preferably 150 nm.

[0012] Preferably according to the present invention, the molar amount of magnesium in the electron transport layer is 10-20% of the molar amount of zinc oxide, preferably 17.6%; the thickness of the electron transport layer is 150-250nm, preferably 200nm.

[0013] According to the preferred embodiment of the present invention, the N-side electrode is Au / Ge / Ni, the thickness of the N-side electrode is 550 nm, wherein the thickness of the Au layer is 300 nm, the thickness of the Ge layer is 150 nm, and the thickness of the Ni layer is 100 nm; the N-side electrode is Ni layer, Ge layer, and Au layer from bottom to top. The Au / Ge / Ni alloy can reduce the ohmic contact of the N-side electrode and reduce the threshold voltage of the device.

[0014] Preferably according to the present invention, the P-side electrode is connected to the positive electrode of the external power supply, and the N-side electrode is connected to the negative electrode of the external power supply.

[0015] The method for preparing the above-mentioned red laser based on the perovskite structure comprises the steps of:

[0016] (1) Obtaining a hole transport layer on the upper surface of the P-side electrode by spin coating and annealing process;

[0017] (2) Obtaining a perovskite active layer on the upper surface of the hole transport layer by spin coating;

[0018] (3) Obtaining an electron transport layer on the upper surface of the perovskite active layer by spin coating and annealing process;

[0019] (4) Obtaining an N-side electrode on the upper surface of the electron transport layer by using a thermal evaporation method and an annealing process;

[0020] (5) A reflective layer is obtained on the lower surface of the P-side electrode using a plasma-assisted evaporation process.

[0021] According to a preferred embodiment of the present invention, in step (1), the preparation method of the hole transport layer is as follows:

[0022] Will Ni (NO 3 ) 2 6H 2 O、Sc(NO 3 ) 3 6H 2 O is dissolved in deionized water; NaOH aqueous solution is added to adjust the pH to 10, stirred, washed by centrifugation, and dried to obtain a colloidal precipitate; nickel oxide doped with scandium element powder is obtained by calcination; the nickel oxide doped with scandium element powder is dispersed in water, spin-coated on the upper surface of the P-side electrode, and annealed to obtain a hole transport layer.

[0023] Preferably, Sc(NO 3 ) 3 6H 2The molar amount of O is Ni (NO 3 ) 2 6H 2 O molar amount of 4-6%, preferably 5%; Ni(NO 3 ) 2 6H 2 The mass ratio of O and deionized water is 1:15-25, preferably 1:20; the concentration of the NaOH aqueous solution is 15-25 mg / mL, preferably 20 mg / mL; the stirring time is 5-15 min, preferably 10 min; the calcination temperature is 250-300° C., preferably 275° C., the calcination atmosphere is air, and the calcination time is 1-3 h, preferably 2 h; the annealing temperature is 350-450° C., the annealing atmosphere is air, and the annealing time is 5-15 min, preferably 10 min.

[0024] Preferably, according to the present invention, in step (2), the preparation method of the perovskite active layer is as follows:

[0025] i. Cs 2 CO 3 , oleic acid and octadecene are fully mixed and dissolved to obtain Cs-oleate;

[0026] ii. Fully mixing Se powder and tributyl phosphine to dissolve to obtain Se-tributyl phosphine;

[0027] iii. PbBr 2 、PbI 2 and octadecene, add oleic acid and oleylamine under a protective atmosphere, and after being fully dispersed, heat to 170-180°C, add Se-tributylphosphine; after stirring and heating for 5-15 minutes, quickly inject Cs-oleate, stir and react for 4-6 seconds, immerse the mixture in a cold water bath and immediately cool to room temperature; after centrifugation, disperse the precipitate in hexane or toluene to obtain CsPbBrl 2 / PbSe quantum dot dispersion; under protective atmosphere, CsPbBrI 2 The PbSe quantum dot dispersion is spin-coated on the upper surface of the hole transport layer to obtain a perovskite active layer.

[0028] Preferably, in step i, Cs 2 CO 3 The mass ratio of Se powder to the volume ratio of tributylphosphine is 0.01-0.02:1 g / mL, preferably 0.01482:1 g / mL; in step iii, PbBr 2 The quality of PbI 2The mass ratio of PbBr to octadecene is 0.01-0.03 g:0.05-0.06 g:4-6 mL, preferably 0.023 g:0.0578 g:5 mL; the volume ratio of octadecene, oleic acid and oleylamine is 8-12:1:1, preferably 10:1:1; 2 The mass, volume of Se-tributylphosphine, and volume ratio of Cs-oleate are 0.0:1-0.03g:0.03-0.08mL:0.2-0.6mL; the protective atmosphere is nitrogen or argon.

[0029] According to a preferred embodiment of the present invention, in step (3), the preparation method of the electron transport layer is as follows:

[0030] Zn(CH 3 COO 2 and Mg(CH 3 COO 2 Dissolve in DMSO to obtain a mixed solution 1; drip tetramethylammonium hydroxide aqueous solution into ethanol to obtain a mixed solution 2; mix the mixed solution 1 and the mixed solution 2, stir and react at 45-55° C. for 0.5-2h, and then precipitate with ethyl acetate to obtain a ZnO:Mg nanomaterial; disperse the ZnO:Mg nanomaterial in ethanol, spin-coat it on the upper surface of the perovskite active layer under a protective atmosphere, and then anneal at 300-400° C. under a protective atmosphere for 5-15min to obtain an electron transport layer.

[0031] Preferably, Zn(CH 3 COO 2 and Mg(CH 3 COO 2 The molar ratio of Zn(CH 3 COO 2 The molar ratio of Zn(CH4) to DMSO is 0.05-0.1 mol / L, preferably 0.085 mol / L; the mass concentration of the tetramethylammonium hydroxide aqueous solution is 20-30%, preferably 25%, and the molar ratio of tetramethylammonium hydroxide to ethanol is 0.6-0.7:1 mol / L, preferably 0.625 mol / L; Zn(CH 3 COO 2 The molar ratio of tetramethylammonium hydroxide to tetramethylammonium hydroxide is 1:1.5-2.5, preferably 1:2; and the protective atmosphere is nitrogen or argon.

[0032] Preferably, according to the present invention, in step (4), the annealing temperature is 350-450° C., the annealing atmosphere is nitrogen or argon, and the annealing treatment time is 2-4 min.

[0033] The present invention provides a red laser based on a perovskite structure, the working principle of which is:

[0034] An external power source connects the P-side electrode to its positive electrode and the N-side electrode to its negative electrode, thereby introducing holes into the P-side electrode and electrons into the N-side electrode. These holes are transmitted to the perovskite light-emitting region through the hole transport layer of the P-side electrode, while the electrons enter the same light-emitting region through the electron transport layer of the N-side electrode. In this region, high concentrations of electrons and holes recombine to produce light. This light beam passes through the hole transport layer and is reflected by the reflective layer, returning to the perovskite active layer again. The reflected light interacts with the light generated by the recombination of electrons and holes in the FP optical resonant cavity (between the electron transport layer and the reflective layer) to achieve light enhancement. After being reflected and refracted by the reflective layer, part of the light is released through the ZnO:Mg transmission layer (the electron transport layer of the present invention).

[0035] The technical features and beneficial effects of the present invention are as follows:

[0036] 1. CsPbBrl 2 Perovskite nanocrystals are an excellent optical gain material due to their large optical absorption cross section, large exciton binding energy, high photoluminescence quantum yield and relatively low AR loss. 2 surface, thereby passivating CsPbBrl 2 Surface trap states contribute to enhanced red-light emission of CsPbBrI 2 / PbSe heterojunction nanocrystal (λ=652 nm) photoluminescence intensity. The laser of the present invention improves the carrier transmission efficiency of perovskite quantum dots in the active area and increases the output power and efficiency of the red laser. 2 / PbSe film can maintain bright red color in high humidity environment.

[0037] 2. The combination of the hole transport layer and the electron transport layer of the present invention effectively promotes the migration of carriers and further improves the performance of the laser. The hole transport efficiency of the traditional hole transport layer is suppressed due to the instability of the traditional HTL and PEDOT:PSS under acidic conditions and its unique hygroscopic properties. NiO x It has good chemical stability and can be used as an excellent buffer layer, showing high resistance and conductivity. 3+ Doping pure NiO x The work function of the device is increased from 4.77 eV to 4.99 eV while maintaining high conductivity, significantly improving the hole transport efficiency of the device. 3+ Doped NiO x As an electron transport layer, compared with undoped NiO xThe threshold current of the laser can be significantly reduced and the output power can be significantly enhanced. By in-situ diffusing Mg atoms into the deep part of the ZnO lattice to generate oxygen vacancies, the electron transfer characteristics are promoted, and the conductivity and luminescence performance are improved.

[0038] 3. Compared with the single-layer reflective film, the multi-layer stacked HfO 2 / SiO 2 The reflective film is based on multi-beam interference, making its reflectivity reach 99.5%, which can significantly improve the output power of the device. The Mg-diffused ZnO film maintains a high transmittance of more than 95% in the visible spectrum region and can be used as a transparent film and a high-reflective film HfO 2 / SiO 2 It forms a FP resonant cavity, promotes the optical gain effect of the perovskite layer in the active area, and increases the output power of the laser beam.

[0039] 4. The N-side electrode is designed with an air circulation channel, which can significantly enhance the heat dissipation effect of the chip during operation, thereby extending the service life and reliability of the device, while also improving its luminous efficiency.

[0040] 5. The red laser of the present invention has the advantages of simple structure, simple preparation method, good heat dissipation, high luminous efficiency, high photoluminescence intensity, low threshold current, and high output power. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a structural diagram of a red laser based on a perovskite structure according to the present invention;

[0042] Among them, 1. N-side electrode, 2. electron transport layer, 3. perovskite active layer, 4. hole transport layer, 5. P-side electrode, 6. reflection layer, 7. air circulation channel.

[0043] Figure 2 The present invention uses CsPbBrI 2 / PbSe heterojunction layer (Example 1) and CsPbBrI 2 Electroluminescence spectrum of a red laser with quantum dots (Comparative Example 1) as the perovskite active layer.

[0044] Figure 3 The present invention uses NiO x :5%Sc 3+ (Example 1) and NiO x (Comparative Example 2) Output power as a hole transport layer versus injected current. DETAILED DESCRIPTION

[0045] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.

[0046] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0047] Example 1

[0048] A red laser based on a perovskite structure, such as Figure 1 As shown, it includes, from bottom to top: a reflective layer 6, a P-side electrode 5, a hole transport layer 4, a perovskite active layer 3, an electron transport layer 2 and an N-side electrode 1.

[0049] The reflective layer 6 is made of HfO 2 Layer and SiO 2 The thickness of the reflective layer 6 is 300nm, and the HfO 2 The single layer thickness of the SiO 2 The single layer thickness of the HfO 2 The layer is in close contact with the lower surface of the P-side electrode 5.

[0050] The P-side electrode 5 is an ITO conductive glass, and an indium tin oxide material with a thickness of 200 nm is grown on the glass surface. The total thickness of the P-side electrode 5 is 300 μm.

[0051] The hole transport layer 4 is nickel oxide doped with scandium, wherein the molar amount of the scandium element is 5% of the molar amount of nickel oxide; the thickness of the hole transport layer 4 is 200 nm.

[0052] Perovskite active layer 3 is CsPbBrl 2 / PbSe heterojunction layer; the thickness of the perovskite active layer 3 is 150 nm.

[0053] The electron transport layer 2 is a zinc oxide layer doped with magnesium, wherein the molar amount of magnesium is 17.6% of the molar amount of zinc oxide; the thickness of the electron transport layer 2 is 200 nm.

[0054] The N-side electrode 1 is Au / Ge / Ni, and the thickness of the N-side electrode 1 is 550 nm, wherein the thickness of the Au layer is 300 nm, the thickness of the Ge layer is 150 nm, and the thickness of the Ni layer is 100 nm; the N-side electrode 1 is Ni layer, Ge layer, and Au layer from bottom to top.

[0055] The N-side electrodes 1 are arranged on both sides of the upper surface of the electron transport layer 2 , and the middle of the N-side electrodes 1 on both sides is an air circulation channel 7 .

[0056] The P-side electrode 6 is connected to the positive electrode of the external power source, and the N-side electrode 1 is connected to the negative electrode of the external power source.

[0057] The electroluminescence spectrum of the red laser based on the perovskite structure in this embodiment is as follows Figure 2The constructed perovskite red laser has excellent red light emission at 652nm, which proves the feasibility of laser construction.

[0058] The output power of the laser in this embodiment varies with the injected current. Figure 3 As shown in the figure, it can be seen that using Sc 3+ Doped NiO x As an electron transport layer, compared with undoped NiO x It can significantly reduce the threshold current of the laser and significantly enhance the output power.

[0059] Example 2

[0060] A method for preparing a red laser based on a perovskite structure as described in Example 1 comprises the following steps:

[0061] (1) Obtaining a hole transport layer 4 on the upper surface of the P-side electrode 5 by spin coating and rapid annealing process;

[0062] Put 3 g Ni (NO 3 ) 2 6H 2 O、Sc(NO 3 ) 3 6H 2 O (where Sc(NO 3 ) 3 6H 2 The molar amount of O is Ni(NO 3 ) 2 6H 2 O molar amount of 5%) was dissolved in 60 mL of deionized water and stirred at room temperature to obtain a clear solution. The solution pH was adjusted to 10 by adding NaOH aqueous solution (20 mg / mL) and stirred for 10 min. The solution was centrifuged and centrifuged three times with deionized water and ethanol to obtain a colloidal precipitate. The colloidal precipitate was dried at 25°C for 12 h and the obtained powder was calcined at 275°C in air atmosphere for 2 h to obtain nickel oxide doped scandium element powder (NiO x :5%Sc 3+ nanoparticles).

[0063] The obtained NiO x :5%Sc 3+ The nanoparticles were dispersed in water at a concentration of 10 mg / mL to form a nano-ink, which was spin-coated on the upper surface of the P-side electrode 5 at 3000 rpm and annealed in air at 400°C for 10 min to obtain a hole transport layer 4 with a thickness of 200 nm.

[0064] (2) obtaining a perovskite active layer 3 on the upper surface of the hole transport layer 4 by a spin coating process;

[0065] By constructing a heterostructure, CsPbBrI with high optical absorption cross-section, exciton binding energy and photoluminescence quantum yield was obtained. 2 / PbSe quantum dots.

[0066] Cs 2 CO 3 (0.814 g), oleic acid (2.5 mL), and octadecene (40 mL) were added into a 100 mL three-necked flask and heated under N 2 Heat to 120℃ under the condition of Cs 2 CO 3 The powder was completely dissolved to obtain Cs-oleic acid. 0.1482 g of Se powder and 10 mL of tributylphosphine were added to a 50 mL three-necked flask, and the Se powder was completely dissolved at 90°C to obtain Se-tributylphosphine. Then, 0.0230 g of PbBr 2 , 0.0578 g PbI 2 and octadecene (5.0 mL) were placed in a 50 mL three-necked flask. Oleic acid (0.5 mL) and oleylamine (0.5 mL) were stirred under N 2 After the solution became clear, the temperature was raised to 175°C and 50 μL of Se-tributylphosphine was added to the solution. After stirring and heating for 10 min, 0.4 mL of Cs-oleate (the stock solution prepared as described above) was quickly injected. After stirring and reacting for 5 s, the mixture was immersed in a cold water bath and immediately cooled to room temperature. After centrifugation, the precipitate was dispersed in hexane to obtain CsPbBrl 2 / PbSe quantum dot dispersion.

[0067] N 2 Atmosphere, CsPbBrI 2 The PbSe quantum dot dispersion was spin-coated on the upper surface of the hole transport layer 4 at 3000 rpm to obtain a perovskite active layer 3 with a thickness of 150 nm.

[0068] (3) obtaining an electron transport layer 2 on the upper surface of the perovskite active layer 3 by spin coating and rapid annealing process;

[0069] ZnO:Mg nanomaterials were synthesized by solution method using tetramethylamine hydroxylate as precipitant. 2.55 mmol Zn(CH 3 COO 2 and 0.45 mmol Mg(CH 3 COO 2Dissolve in 30 ml DMSO at 50°C to obtain mixed solution 1. Then, add 5 mmol of tetramethylammonium hydroxide aqueous solution (mass concentration is 25%) to 8 ml ethanol to obtain mixed solution 2. Mixed solution 1 and mixed solution 2 are mixed, stirred at 50°C for 1 h, and ethyl acetate is added to the mixed solution to precipitate ZnO:Mg nanomaterials, which are then dispersed in ethanol. The above purification process is repeated twice to obtain pure ZnO:Mg nanomaterials.

[0070] The ZnO:Mg nanomaterials were dispersed in ethanol and heated in N 2 In the atmosphere, it is spin coated on the upper surface of the perovskite active layer 3 at 3000 rpm, and then annealed at 350°C in a nitrogen atmosphere for 10 min to obtain a 200 nm thick electron transport layer 2 on the upper surface of the perovskite active layer 3 as an electron transport layer and an optical transmission layer.

[0071] (4) Obtaining an N-side electrode 1 on the upper surface of the electron transport layer 2 by a thermal evaporation method;

[0072] A Ni layer, a Ge layer, and an Au layer are sequentially evaporated on the upper surface of the electron transport layer 2 by a thermal evaporation method, and then annealed at 400°C in a nitrogen atmosphere for 3 minutes to obtain an N-surface electrode 1 with a thickness of 550 nm on the upper surface of the electron transport layer 2, wherein the thickness of the Au layer is 300 nm, the thickness of the Ge layer is 150 nm, and the thickness of the Ni layer is 100 nm.

[0073] (5) A reflective layer 6 is obtained on the lower surface of the P-side electrode 5 by using a plasma-assisted evaporation process.

[0074] Plasma-assisted evaporation process was used to deposit HfO 2 and SiO 2 As a raw material, HfO is first evaporated on the lower surface of the P-side electrode 5. 2 layer, and then evaporated SiO 2 The cycle continues until the reflection layer is obtained.

[0075] Comparative Example 1

[0076] A red laser based on a perovskite structure, as described in Example 1, except that the perovskite active layer 3 is CsPbBrl 2 The other structures and parameters are the same as those in Example 1.

[0077] The preparation method of the above-mentioned red laser based on the perovskite structure is as described in Example 2, except that: the preparation method of the perovskite active layer 3 is as follows:

[0078] Cs 2 CO 3(0.814 g), oleic acid (2.5 mL), and octadecene (40 mL) were added into a 100 mL three-necked flask and heated under N 2 Heat to 120℃ under the condition of Cs 2 CO 3 The powder was completely dissolved to obtain Cs-oleic acid.

[0079] Take 0.0230 g PbBr 2 , 0.0578 g PbI 2 and octadecene (5.0 mL) were placed in 50 mL three-necked flasks. 2 Oleic acid (0.5 mL), oleylamine (0.5 mL) and 50 μL tributylphosphine were injected under atmosphere. After the solution became clear, the temperature was raised to 175 °C and Cs-oleate (0.4 mL stock solution prepared as described above) was quickly injected. After stirring for 5 s, the reaction mixture was immersed in a cold water bath and immediately cooled to room temperature. After centrifugation, the precipitate was dispersed in hexane to obtain CsPbBrl 2 Quantum dot dispersion.

[0080] N 2 Atmosphere, CsPbBrI 2 The quantum dot dispersion was spin-coated on the upper surface of the hole transport layer 4 at 3000 rpm to obtain a perovskite active layer 3 with a thickness of 150 nm.

[0081] The other steps and conditions are the same as in Example 2.

[0082] The electroluminescence spectrum of the red laser in this comparative example is as follows Figure 2 , CsPbBrl 2 layer as a perovskite active layer, the photoluminescence intensity of the laser is reduced.

[0083] Comparative Example 2

[0084] A red laser based on a perovskite structure is as described in Example 1, except that the hole transport layer 4 is nickel oxide with a thickness of 200 nm. Other structures and parameters are the same as in Example 1.

[0085] The preparation method of the above-mentioned red laser based on the perovskite structure is as described in Example 2, except that: the preparation method of the hole transport layer 4 is as follows:

[0086] Put 3 g Ni (NO 3 ) 2 6H 2O was dissolved in 60 mL of deionized water and stirred at room temperature to obtain a clear solution. The solution pH was adjusted to 10 by adding NaOH aqueous solution (20 mg / mL) and stirred for 10 min, then centrifuged and centrifuged three times with deionized water and ethanol to obtain a colloidal precipitate. The colloidal precipitate was dried at 25°C for 12 h and the obtained powder was calcined at 275°C in air atmosphere for 2 h to obtain nickel oxide powder.

[0087] The obtained nickel oxide powder was dispersed in water at a concentration of 10 mg / mL to form a nano-ink, which was spin-coated on the upper surface of the P-side electrode 5 at 3000 rpm and annealed in air at 400° C. for 10 min to obtain a hole transport layer 4 with a thickness of 200 nm.

[0088] The other steps and conditions are the same as in Example 2.

[0089] The output power of the comparative laser varies with the injected current. Figure 3 shown.

Claims

1. A red laser based on a perovskite structure, characterized in that: From bottom to top, it includes: reflective layer, P-side electrode, hole transport layer, perovskite active layer, electron transport layer and N-side electrode; The reflective layer is formed by alternately stacking HfO2 layers and SiO2 layers, the thickness of the reflective layer is 250-350nm, the single layer thickness of the HfO2 layer is 25-35nm, and the single layer thickness of the SiO2 layer is 15-25nm; the HfO2 layer is close to the lower surface of the P-side electrode; the hole transport layer is nickel oxide doped with scandium, and the molar amount of scandium in the hole transport layer is 4-6% of the molar amount of nickel oxide; the perovskite active layer is a CsPbBrl2 / PbSe heterojunction layer; the electron transport layer is a zinc oxide layer doped with magnesium, and the molar amount of magnesium in the electron transport layer is 10-20% of the molar amount of zinc oxide; the N-side electrodes are arranged on both sides of the upper surface of the electron transport layer, and the middle of the N-side electrodes on both sides is an air circulation channel; The preparation method of the perovskite active layer is as follows: i. Fully mix and dissolve Cs2CO3, oleic acid and octadecene to obtain Cs-oleate; ii. Fully mixing Se powder and tributyl phosphine to dissolve to obtain Se-tributyl phosphine; iii. PbBr2, PbI2 and octadecene are mixed, oleic acid and oleylamine are added under a protective atmosphere, and after being fully dispersed, the temperature is raised to 170-180°C, and Se-tributylphosphine is added; after stirring and heating for 5-15 minutes, Cs-oleate is quickly injected, and after stirring and reacting for 4-6 seconds, the mixture is immersed in a cold water bath and immediately cooled to room temperature; after centrifugation, the precipitate is dispersed in hexane or toluene to obtain a CsPbBrl2 / PbSe quantum dot dispersion; under a protective atmosphere, the CsPbBrI2 / PbSe quantum dot dispersion is spin-coated on the upper surface of the hole transport layer to obtain a perovskite active layer; The preparation method of the electron transport layer is as follows: Dissolve Zn(CH3COO)2 and Mg(CH3COO)2 in DMSO to obtain a mixed solution 1; drip tetramethylammonium hydroxide aqueous solution into ethanol to obtain a mixed solution 2; mix the mixed solution 1 and the mixed solution 2, stir and react at 45-55°C for 0.5-2h, and then precipitate with ethyl acetate to obtain a ZnO:Mg nanomaterial; disperse the ZnO:Mg nanomaterial in ethanol, spin-coat it on the upper surface of the perovskite active layer under a protective atmosphere, and then anneal at 300-400°C in a protective atmosphere for 5-15min to obtain an electron transport layer.

2. The red laser based on the perovskite structure according to claim 1, characterized in that: The P-side electrode is ITO conductive glass with a thickness of 250-350 μm.

3. The red laser based on the perovskite structure according to claim 1, characterized in that: The thickness of the hole transport layer is 150-250 nm.

4. The red laser based on the perovskite structure according to claim 1, characterized in that: The thickness of the perovskite active layer is 100-200nm.

5. The red laser based on the perovskite structure according to claim 1, characterized in that: The thickness of the electron transport layer is 150-250 nm.

6. The red laser based on the perovskite structure according to claim 1, characterized in that: The N-side electrode is Au / Ge / Ni, and the thickness of the N-side electrode is 550 nm, of which the thickness of the Au layer is 300 nm, the thickness of the Ge layer is 150 nm, and the thickness of the Ni layer is 100 nm; the N-side electrode is Ni layer, Ge layer, and Au layer from bottom to top.

7. The red laser based on the perovskite structure according to claim 1, characterized in that: The P-side electrode is connected to the positive electrode of the external power supply, and the N-side electrode is connected to the negative electrode of the external power supply.

8. The method for preparing a red laser based on a perovskite structure according to any one of claims 1 to 7, comprising the steps of: (1) Obtaining a hole transport layer on the upper surface of the P-side electrode by spin coating and annealing process; (2) Obtaining a perovskite active layer on the upper surface of the hole transport layer by spin coating; (3) Obtaining an electron transport layer on the upper surface of the perovskite active layer by spin coating and annealing process; (4) Obtaining an N-side electrode on the upper surface of the electron transport layer by using a thermal evaporation method and an annealing process; (5) A reflective layer is obtained on the lower surface of the P-side electrode using a plasma-assisted evaporation process.

9. The method for preparing a red laser based on a perovskite structure according to claim 8, characterized in that: In step (1), the preparation method of the hole transport layer is as follows: Dissolve Ni (NO3)2·6H2O and Sc(NO3)3·6H2O in deionized water; add NaOH aqueous solution to adjust the pH to 10, stir, wash by centrifugation, and dry to obtain a colloidal precipitate; calcine to obtain nickel oxide doped with scandium element powder; disperse the nickel oxide doped with scandium element powder in water, spin-coat it on the upper surface of the P-side electrode, and anneal to obtain a hole transport layer.

Citation Information

Patent Citations

  • Electric pumping perovskite laser

    CN111162446A

  • PEI (polyethyleneimine) based high-efficiency perovskite quantum dot light-emitting thin film and preparation method thereof

    CN105720205A

  • A perovskite battery and a glass cover plate thereof, which have the functions of wide spectrum antireflection and ultraviolet filter

    CN109065732A

  • Electric pumping perovskite composite cavity laser

    CN109687290A

  • Magnesium-doped zinc oxide, preparation method and application thereof, preparation method of electron transport layer and perovskite photoelectric detector

    CN117534114A